Cord blood cytokine levels in focal early-onset neonatal infection after preterm premature rupture of membranes - Kurokawa, Cilmery Suemi [UNESP]; Hashimoto, Miriam [UNESP]; Rugolo, Ligia Maria Suppo de Souza [UNESP]; Bentlin, Maria Regina [UNESP]; Golin, Marjorie de Assis [UNESP]; Peraçoli, José Carlos [UNESP]; da Silva, Marcia Guimarães [UNESP]; Corrente, José Eduardo [UNESP]; Fekete, Saskia Maria Wiegerinck [UNESP] (My University, 2013)
This study aimed to evaluate the levels of pro- and anti-inflammatory cytokines in umbilical cord blood of preterm neonates who developed focal early-onset infection (EOI) after preterm premature rupture of membranes (PPROM). This is a prospective study conducted on 46 preterm infants from mothers with PPROM. The cytokines were measure by flow cytometry. Newborns were classified into two groups as focal EOI (n=19) and non-infected (n=27). Interleukin (IL)-6 and IL-8 levels were higher, whereas IL-10 and IL-12 p70 levels were lower in the EOI when compared to the non-infected group. The best combination of cytokines was IL-6+IL-8, with a diagnostic accuracy of 0.97. Focal EOI after PPROM is associated with increased levels of IL-6 and IL-8 and diminished IL-10 and IL-12 in the cord blood of preterm infants. Combined assessment of IL-6 and IL-8 in cord blood may provide an additional tool for identifying preterm infants who develop EOI after PPROM.
Keywords: Cytokine; Early infection; In vivo inflammation; Infant; Innate immunity; Premature